Combination of Different Kinds of Materials for Hybrid Composites: A Brief Review - Gupta H.S.; Verma D.; Verma A. (My University, 2025)
In the recent decades, the hybrid composites have been subject of interest to the researchers and engineers from an economic consistency and environmental based. This novel class of materials is made by two or more than two distinct fibers or fillers reinforced in an appropriate polymer matrix to form an inventive material with better properties comparable to those of conventional materials. Therefore, in order to achieve better structural design and properties, a good selection of the hybrid composites ingredients and their properties need to be thoroughly explored. This chapter aims to provide an overview of different kinds of materials used for hybrid composites and how their properties and applications in various fields. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.